The solution of oil leakage on the joint surface of the combustion chamber casing and the rear jacket. Issue 5 (January 2021) - Zeng, Xianghu; Xu, Ying; Zhang, Yue; Xu, Zhanghuan
Abstract: In order to solve the problem of oil leakage at the flange bolted connection of the casing of combustion chamber, an implementation solution was proposed in this paper. Firstly, a simplified flange bolted connection finite element model was established in ANSYS based on the actual size of the casing. Then, the deformation of the flange joint surface under two different forms of load was analyzed. Finally, according to calculation results, the suggestion of adding gasket was proposed to improve sealing performance of casing, and the sealing effect of gaskets of different thicknesses is also studied. This article provided a reference for improving the oil leakage problem of the casing flange bolted connection.